Communicating at work - Ronald B. Adler (McGraw Hill Higher Education)
Berisi Quizzes, Flashcards, Communications Concepts Video, Business Document Tempalte, Outline Tutor, Learning Assessment Tool, Study skill Primer, Glossary, Online Learning Center.